UNWAHA Cooperative Digital Marketing Automation Based on BOT Engine - Siti Sufaidah; Muhammad Al Faqih (NEWTON: Networking and Information Technology, 2022)
So far, the University KH A. Wahab Hasbullah cooperative service system. to customers is done manually even small things such as customer questions to cooperatives regarding the availability and price of an item must be done manually and of course it is very disturbing ease of shopping and tends to waste time for customers. Telegram messenger is a social messenger or chat media that has a lot of unique features that are free so it is very beneficial to use for the general public, one of its unique features is its telegram-bot (Telegram BOT). Telegram BOT Api is a robot created with a program that can perform many instructions given by the creator or user, this bot itself is just a telegram account running on software that has artificial intelligence features. This telegram api bot offers developers to make it easier to retrieve data and process it into useful information. Telegram bot itself is divided into two, namely the mobile version (telegram bot) and the web version. The result of this research is that this mobile application is managed using a webhook as the communication method. This method is used because it is very easy and bots do not have to update data regularly because one of them is placed in the Uniform Resource Locator (URL). And if there is an incoming message, it will be directly displayed at the specified URL and will then be forwarded to the bot for processing. This telegram api bot offers developers to make it easier to retrieve data and process it into useful information. Telegram bot itself is divided into two, namely the mobile version (telegram bot) and the web version. The result of this research is that this mobile application is managed using a webhook as the communication method. This method is used because it is very easy and bots do not have to update data regularly because one of them is placed in the Uniform Resource Locator (URL). And if there is an incoming message, it will be directly displayed at the specified URL and will then be forwarded to the bot for processing. This telegram api bot offers developers to make it easier to retrieve data and process it into useful information. Telegram bot itself is divided into two, namely the mobile version (telegram bot) and the web version. The result of this research is that this mobile application is managed using a webhook as the communication method. This method is used because it is very easy and bots do not have to update data regularly because one of them is placed in the Uniform Resource Locator (URL). And if there is an incoming message, it will be directly displayed at the specified URL and will then be forwarded to the bot for processing. The result of this research is that this mobile application is managed using a webhook as the communication method. This method is used because it is very easy and bots do not have to update data regularly because one of them is placed in the Uniform Resource Locator (URL). And if there is an incoming message, it will be directly displayed at the specified URL and will then be forwarded to the bot for processing. The result of this research is that this mobile application is managed using a webhook as the communication method. This method is used because it is very easy and bots do not have to update data regularly because one of them is placed in the Uniform Resource Locator (URL). And if there is an incoming message, it will be directly displayed at the specified URL and will then be forwarded to the bot for processing.